Chicken Soup For The Teenage Soul On Tough Stuff: Stories Of Tough Times And Lessons Learned - Jack Canfield
This latest offering in the best-selling Chicken Soup for the Teenage Soul series explores a host of challenges faced by today's teens. Within its pages teens will find portraits of life's complexities expressed from the viewpoint of their peers. Teen contributors share their thoughts and feelings on difficult issues, ranging from poor self-image to thoughts of suicide, from family discord to coping with the loss, from peer pressure to school violence. Teens ranked stress as one of their top concerns (along with child abuse and STDs). Oftentimes, the pressure can feel overwhelming, whether they involve worrying about an upcoming test, competition sports, family responsibilities, dating, or more extreme issues such as depression, suicide and school violence. The first three volumes of the Teenage Soul series and the companion journal illustrate the ongoing popularity of this series (unit sales exceed 11 million). Chicken Soup for the Teenage Soul on Tough Stuff and the Spring 2001 release Teenage Soul Letters will undoubtedly follow suit as the next best-sellers in a phenomenally popular series.